EFFECT OF ERANDAPATHRAKSHARA (RICINUS COMMUNIS LINN.) ALONG WITH HINGU (FERULA NARTHEX LINN.) IN DYSLIPIDEMIA (International Journal of Ayurveda and Pharma Research, 2017)
Cardiovascular diseases (CVD) are of prime importance among lifestyle disease and dyslipidemia is an independent and modifiable risk factor for CVD, together with smoking and sedentary habits, fatty diets and stressful life situations. Dyslipidemia can be included under the term Medovikaras in Ayurveda. . A combination of Erandapathrakshara (Ricinus communis Linn) and Hingu (Ferula narthex Linn) is mentioned in Bhavaprakasa for curing Medovriddhi. At present era, many modern medications are available for curing the elevated lipid levels. But they cause many side effects which are extremely hazardous to human health. So a clinical study is selected with an interest to revalidate the ancient scientific knowledge. Genuine samples of both Eranda (Ricinus communis Linn) and Hingu (Ferula narthex Linn) were collected. Thekshara of Erandapathra and powder of purified Hingu were given to the patient with Mandam (supernatant liquid portion of rice soup) as Anupaana for a period of 1 month. Patients of both sexes in the age group of 30-60 years with serum LDL above 130mg/dl, non HDL-C above 139mg/dl from OPD. The statistical analysis of changes in Lipid profile values before treatment, after treatment, and after follow up are the assessment criteria. Trial drugs were found to be effective in reducing T. Cholesterol, LDL, triglycerides and Non-HDL-c but not effective in reducing VLDL and increasing HDL and no side effects were observed during study period. From the present study we can conclude that the trial drugs were effective and can be used safely in clinical practice in future.